2022
DOI: 10.1021/acs.orglett.2c00231
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Mediated Oxidative Fragmentation of Ethers and Acetals by Means of Fe(III) Catalysis

Abstract: A new method employing iron(III) acetylacetonate along with visible light is described to effect oxidative ring opening of cyclic ethers and acetals with unparalleled efficiency. The method allows for a photocatalytic radical chemistry approach to functionalize relatively inert cyclic ethers into useful synthetic intermediates. The methodology sheds further light on the use of underexplored iron complexes in visible-light photochemical contexts and illustrates that simple Fe(III) complexes can initiate redox p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Observation of slow corrosion of the metallic needle, likely due to formation of HBr during the progression of the reaction, is consistent with this assumption. In our previous efforts, we have observed that ring-opening of cyclic ethers can be facilitated under similar conditions, in the presence of trace amount of transition metals, 26 which further supports the hypothesis of metal catalysis. Therefore, the metal composition of the needle was evaluated by XRF, and major metals present in the needle were tested in our system (see ESI †).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Observation of slow corrosion of the metallic needle, likely due to formation of HBr during the progression of the reaction, is consistent with this assumption. In our previous efforts, we have observed that ring-opening of cyclic ethers can be facilitated under similar conditions, in the presence of trace amount of transition metals, 26 which further supports the hypothesis of metal catalysis. Therefore, the metal composition of the needle was evaluated by XRF, and major metals present in the needle were tested in our system (see ESI †).…”
supporting
confidence: 73%
“…This process is further facilitated by an iron catalyzed generation of both ˙CCl 3 and carbocation under blue-light irradiation. 26 Lastly, the ring-opening event of carbocation by bromide ion provides the final bromoketone.…”
mentioning
confidence: 99%
“…We have recently in our laboratory disclosed an Fe-catalyzed oxidative fragmentation of ethers and acetals giving distally brominated ketones or esters, respectively (Scheme ). Similar to that in the ATRA reactions, the catalyst engages BrCCl 3 reductively, giving a trichloromethyl radical and a bromide ion after mesolytic cleavage. But contrary to an addition, the trichloromethyl radical abstracts a hydrogen from the substrate to generate an α-oxyradical.…”
Section: Resultsmentioning
confidence: 97%
“…For full exploration of the utility of the heterogenized catalyst, four reactions that constitute examples of both oxidative and reductive quenching mechanisms were selected. These include reductive dehalogenation, atom-transfer radical addition (ATRA), oxidative fragmentation of ethers and acetals, and aerobic oxidative hydroxylation of boronic acids (Figure ). Additionally, we also explored the olefin E -to- Z isomerization of cinnamates to evaluate the performance of an energy-transfer pathway from the excited triplet state of the catalyst, *PC­(T 1 ), to generate the excited triplet state of the alkene …”
Section: Resultsmentioning
confidence: 99%
“…The active species can oxidize/reduce the substrates, generating the corresponding active radicals. Though some reports pointed out that these active species decayed back to their ground states extremely rapid, 7b oxidative/reductive quenching can still happen through initial propagation or other processes. For the majority of the intramolecular charge transfer modes (Scheme 1 C), ligand–metal charge transfer (LMCT) processes realize the desired homolysis of the metal–substrate bonds.…”
Section: Visible-light-induced Fe-catalyzed Reactionsmentioning
confidence: 99%